Does the application of kinesiotape change scapular kinematics in healthy female handball players? - Van Herzeele, M.; van Cingel, R.; Maenhout, A.; De Mey, K.; Cools, A. (International Journal of Sports Medicine, 2013)
Elastic taping is widely used in sports medicine for correcting functional alignment and muscle recruitment. However, evidence regarding its influence on scapular dynamic positioning is scarce. This study aimed to investigate the effect of a specific kinesiotaping method on scapular kinematics in female elite handball players without shoulder complaints. 25 athletes (18.0±1.5 years) active in the highest national division were recruited. All subjects received an elastic adhesive tape (K-active tape©) with the purpose to correct scapular position. 3-dimensional scapular motion measurements were performed (Fastrak®) during humeral elevation in the sagittal, frontal and scapular plane. The results showed that taping has a moderate to large effect (Cohen`s d>0.7) towards scapular posterior tilting, in all 3 planes of humeral movement and for all angles of elevation (mean posteriorizing effect of 4.23°, 3.23° and 4.33° respectively for elevation in the sagittal, frontal and scapular plane, p<0.001). In addition, taping also moderately increased the scapular upward rotation at 30°, 60° and 90° of humeral abduction (mean increase of 2.90°, Cohen`s d>0.7). Together these results suggest that kinesiotape application causes positive changes in scapular motion. This could support its use in sports medicine for preventing shoulder problems in overhead athletes.